2005
DOI: 10.1111/j.1460-9568.2005.04358.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological stress increases histone H3 phosphorylation in adult dentate gyrus granule neurons: involvement in a glucocorticoid receptor‐dependent behavioural response

Abstract: Chromatin remodelling associated with transcriptional activation of silent genes involves phosphorylation at Serine-10 and acetylation at Lysine-14 in the N-terminal tails of the nucleosomal protein histone H3. We have identified neurons predominantly in the dentate gyrus showing a speckled nuclear immunoreactivity pattern for phosphorylated histone H3 [i.e. P(Ser10)-H3] and phospho-acetylated histone H3 [i.e. P(Ser10)-Ac(Lys14)-H3]. Forced swimming increased the number of P(Ser10)-H3-positive [P(Ser10)-H3+] n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
136
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 61 publications
(95 reference statements)
19
136
1
1
Order By: Relevance
“…In view of this complexity, it is difficult to develop valid animal models to study this disorder (Frazer and Morilak, 2005). However, one of the main predisposing factors in development of depression is exposure to traumatic and stressful events (see Kessler, 1997;Bilang-Bleuel et al, 2005), resulting in a dysregulated response of the hypothalamus-pituitaryadrenal (HPA) axis (see Holsboer, 2001). Moreover, depression is often viewed as inability to cope with stress (see Anisman and Zacharko, 1990;Kessler, 1997).…”
Section: Depression-like Behavior In Rats and The Fstmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of this complexity, it is difficult to develop valid animal models to study this disorder (Frazer and Morilak, 2005). However, one of the main predisposing factors in development of depression is exposure to traumatic and stressful events (see Kessler, 1997;Bilang-Bleuel et al, 2005), resulting in a dysregulated response of the hypothalamus-pituitaryadrenal (HPA) axis (see Holsboer, 2001). Moreover, depression is often viewed as inability to cope with stress (see Anisman and Zacharko, 1990;Kessler, 1997).…”
Section: Depression-like Behavior In Rats and The Fstmentioning
confidence: 99%
“…However, exposure to inescapable swimming may not be sufficiently strong to induce long-lasting depression-like symptoms in the normal rat. Nevertheless, the FST does represent an acute stressful event, since it is associated with a profound increase in adrenocorticotropin and corticosterone levels (Bilang-Bleuel et al, 2002;Rittenhouse et al, 2002), as well as with neurochemical and morphological changes in the hippocampus (Bilang-Bleuel et al, 2005) and prefrontal cortex (Izquierdo et al, 2006). Importantly, the immobility response in the FST can be prevented by glucocorticoid antagonists (Jefferys and Funder, 1987;Korte et al, 1996;Bilang-Bleuel et al, 2005) and various types of antidepressant treatments, including tricyclic antidepressants, monoamine oxidase inhibitors, SSRIs, and NA reuptake inhibitors (see Borsini and Meli, 1988).…”
Section: Depression-like Behavior In Rats and The Fstmentioning
confidence: 99%
“…However, alternative mechanisms, which, for example, imply an epigenetic control of neurotrophin transcription, could be considered. In fact it has been shown that forced swim stress increases the phosphorylation of histone-3 through a GR-dependent mechanism (Bilang-Bleuel et al, 2005) and posttranslational modifications of histones Stress-dependent BDNF modulation after duloxetine(phosphorylation and/or acetylation) appear to be relevant for neurotrophin transcription, particularly for exons IV and VI (Tsankova et al, 2006).…”
Section: Stress-dependent Bdnf Modulation After Duloxetine R Molteni mentioning
confidence: 99%
“…These circumstances foster both rapid and delayed (protein-synthesisdependent) synaptic delivery of AMPAR and/or NMDAR subunits [39,40,42,51]. A subsequent and/or additional pathway involves NMDAR-triggering of signaling cascades leading to (epi)genomic changes in gene transcription [14,[73][74][75]80], with at least one of these targets leading to increased probability of glutamate release [80]. In general, rapid effects are mediated by membrane-bound MRs or GRs, whereas delayed genomic effects are mediated by nuclear-localized GRs.…”
Section: Opinionmentioning
confidence: 99%
“…Specifically, evidence has been presented that glucocorticoid-induced enhancement of memory consolidation (as assessed in a forced swim test) took place through the activation of NMDARs and the downstream mitogen-activated protein kinase (MAPK) pathway, including activation of ERK (extracellular signal-regulated kinase)/MSK (mitogen and stress-activated protein kinase) and transcription factor Elk-1 in the dentate gyrus of the hippocampus [73][74][75]. Activation of this pathway was demonstrated to result in epigenetic changes including enhanced histone acetylation [73][74][75]. These epigenetic mechanisms were only efficient in the presence of activated GRs and they acted in synergy with NMDAR activation [74] (Figure 1e).…”
Section: Trends In Neurosciencesmentioning
confidence: 99%